Manual for sweetpotato pre‐basic seed production using the sandponics system - Makokha, P.; Ssali, R.T.; Otazu, V.; Wanjala, Bramwel W.; Rajendran, S.; Chiona, M.; Masamba, Kingsley; McEwan, M.; Low, Jan W. (International Potato Center, 2019)
This manual explains the procedures involved in setting up the sandponics system and managing it to multiply sweetpotato pre‐basic seed to ensure a dependable supply of high‐quality planting materials.